Sequential Congruency Effects of Reverse Stroop Interference on Event-Related Potential Components for Go- and Nogo-Stimuli - Suzuki, Kota (Frontiers in Psychology, 2021)
Sequential congruency effects are observed in interference tasks, in which RTs are shorter for congruent stimuli preceded by congruent (cC) than incongruent stimuli (iC), and RTs are longer for incongruent stimuli preceded by congruent (cI) than incongruent stimuli (iI). These effects are interpreted as resulting from incongruent stimuli triggering attentional control in the next trial, which reduces cognitive control. The aim of this study was to examine sequential congruency effects on ERP components for Go- and Nogo-stimuli. We used the hybrid reverse Stroop Go/Nogo task. The stimuli were Kanji characters, “赤” (i.e., red) and “青” (i.e., blue ) painted in congruent and incongruent colors. Participants responded to one of the two characters (i.e, the Go-stimulus) and stop responding to the other character (i.e., the Nogo-stimulus). Results indicated that the Nogo-N1 was reduced by trials preceded by incongruent stimuli compared to congruent ones, suggesting that color processing was inhibited by attentional control. However, there was no reduction in the Go-N1. Moreover, the Nogo-N2 amplitudes were larger for cI than iI and iC than cC. On the other hand, the Go-N2 was not modulated by sequential modulation effects, which was lower for incongruent stimuli than congruent stimuli. These results indicate that the Nogo-N2 is involved in cognitive control, whereas the Go-N2 is associated with selection processing. These findings suggest that sequential congruency effects’ modulation of N1 and N2 required the response inhibition task demand. However, Go-P3 and Nogo-P3 amplitudes were the largest for cI. Therefore, the ERP components’ time range might be related to the interaction effect’s susceptibility between response inhibition task demand and sequential congruency effects.